Aboriginal people with chronic HCV: The role of community health nurses for improving health-related quality of life. Issue 3 (June 2020) - Rashidi, Amineh; Higgs, Peter; Carruthers, Susan
Abstract: Introduction: There is a lack of knowledge about Health-Related Quality of Life (HRQL) of Aboriginal Australians with self-reported hepatitis C infection in Western Australia. This marginalised group of people is disproportionally affected by the hepatitis C virus (HCV) for which there is no preventative vaccine. This study provides data that help understand the long-term consequences of living with HCV infection within the Aboriginal community. It outlines opportunities for nursing interventions for hepatitis care that focus on supporting mental health and drug and alcohol issues within this population. Methods: We surveyed 123 Aboriginal people living with HCV in a community setting. Survey data included demographics, drug use history, length of time since diagnosis, changes in lifestyle since diagnosis, fatigue, social support, alcohol consumption, and physical and mental health measures. Results: Most participants reported amphetamine injecting frequently in the last six months and their duration of injecting drug ranged from 8 to more than 11 years. Additionally, half of the participants were classified as high-risk alcohol users. Overall 52% of participants were in poor physical and 60% of participants were in poor mental health. Discussion: This survey of Aboriginal people with self-reported hepatitis C infection indicates substantial problems of mental and physical comorbidities among this population. Conclusion: There is a need for the development of HCV community clinics in Aboriginal health care settings with trained Aboriginal community health nurses to reduce problematic alcohol consumption, assess liver health and subsequently provide HCV treatment in a culturally appropriate way.